A study on the effects of inadequate sport equipment and facilities on sports development and academic performance in primary schools: a case study of Bwari area council of Abuja-Nigeria - M. Sanni, Dahiru; Ede, Caleb; A. Fashina, Adebayo (SPC Journal of Education, 2018)
Since physical education was designed to help students develop their physical, mental, and social abilities, there is a need to explore the development of sport in Nigerian schools, particularly, in the primary schools. This paper presents the results of a survey that provides insights on the effect of inadequate sporting facilities and equipment on the development of sports in primary schools in Bwari Area Coun-cil, FCT-Abuja, Nigeria. The six month questionnaire study was carried out in fifteen selected primary schools from the four educational zones in the Area Council. The questionnaire was administered to 195 teachers from the selected schools before the data collected was analyzed using simple percentage approach. The study identifies the factors that influence non-participation of schools in this Area council in sport competitions. The academic and social impacts of providing adequate sporting activities, equipment and facilities are discussed before recommending the appropriate programs that can help enhance sport development at the primary school level in Bwari Area Coun-cil and Nigeria at large.Â